A - Beskeen, David W. (Course Technology, 2003)
See how far your imagination can take you as you explore Web design possibilities with Adobe Photoshop, LiveMotion, and GoLive. Begin your journey with Photoshop as you take an up-close look at layers, images, and selections. Learn how color techniques such as blending and effects can transform your project. Then it's on to LiveMotion as you work with color, effects, and rollovers. Create 3D effects, animate objects, and add sound to your animations. Finish things up by creating a new GoLive site: build a Home Page, add images, and format your text. Test your newfound skills as you animate Photoshop layers in LiveMotion and use LiveMotion objects in GoLive. With a little creativity, some solid design principles, and truly powerful design tools, the possibilities are endless!